2011
DOI: 10.1182/blood-2011-04-351239
|View full text |Cite
|
Sign up to set email alerts
|

Targeting survivin overcomes drug resistance in acute lymphoblastic leukemia

Abstract: Relapse of drug-resistant acute lymphoblastic leukemia (ALL) has been associated with increased expression of survivin/BIRC5, an inhibitor of apoptosis protein, suggesting a survival advantage for ALL cells. In the present study, we report that inhibition of survivin in patientderived ALL can eradicate leukemia.Targeting survivin with shRNA in combination with chemotherapy resulted in no detectable minimal residual disease in a xenograft model of primary ALL. Similarly, pharmacologic knock-down of survivin usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 46 publications
0
98
0
Order By: Relevance
“…We demonstrated that expression of both of these genes could be decreased after vorinostat exposure. Improving chemosensitivity by performing knock-down experiments of BIRC5 has been shown by us 26 and others 29 and has further supported its role in chemoresistance. Similarly, down-regulation of genes such as NR3C1 and BTG1 have been linked previously to glucocorticoid resistance, 30 and we observed herein increased expression of these genes after vorinostat treatment.…”
Section: Discussionmentioning
confidence: 70%
“…We demonstrated that expression of both of these genes could be decreased after vorinostat exposure. Improving chemosensitivity by performing knock-down experiments of BIRC5 has been shown by us 26 and others 29 and has further supported its role in chemoresistance. Similarly, down-regulation of genes such as NR3C1 and BTG1 have been linked previously to glucocorticoid resistance, 30 and we observed herein increased expression of these genes after vorinostat treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Survivin is a protein that is cell cycle-regulated with a robust increase in the G2/M phase in cancer cells (12,13). Survivin is known to be overexpressed and related with more aggressive behavior, increased tumor recurrence, chemotherapy resistance and increased survival in various tumors (6,(14)(15)(16)(17)(18)(19)(20)(21). As a prognostic factor, survivin expression is significantly associated with a poor clinical outcome in certain types of cancer, including liver (2), colorectal and breast (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Patient ALL samples and cell lines Primary pre-B ALL samples were used for in vivo and in vitro as described in "Supplemental Methods." 12 …”
Section: In Vitro and In Vivo Studies With Integrin Alpha4mentioning
confidence: 99%
“…12 Quantitative reverse transcriptase-polymerase chain reaction (PCR), PCR, and flow cytometry Information is listed in "Supplemental Methods" and supplemental Tables 1 and 2. [13][14][15] Patient ALL samples and cell lines Primary pre-B ALL samples were used for in vivo and in vitro as described in "Supplemental Methods."…”
Section: In Vitro and In Vivo Studies With Integrin Alpha4mentioning
confidence: 99%